A gust of photo-philia : photography in the art museum - Moschovi, Alexandra (Lieven Gevaert series, 2020)
Photography was long regarded as a "middlebrow" art by the art institution. Yet, at the turn of the millennium it became the hot, global art of our time. In this book - part institutional history, part account of shifting photographic theories and practices - Alexandra Moschovi tells the story of photography?s accommodation in and as contemporary art in the art museum. Archival research of key exhibitions and the contrasting collecting policies of MoMA, Tate, the Guggenheim, the V&A, and the Centre Pompidou offer new insights into how art as photography and photography as art have been collected and exhibited since the 1930s. Moschovi argues that this accommodation not only changed photography?s status in art, culture, and society, but also played a significant role in the rebranding of the art museum as a cultural and social site